Assessing digit preference and age heaping in Nepal: Evidence from the census 2021 : Assessing digit preference and age heaping in Nepal - Pandit, Sudesh; Thasineku, Om Chandra; Adhikari, Ramesh; Sharma, Sushil; Paudel, Pitambar (Nepal Journal of Multidisciplinary Research, 2026)
Background Accurate information regarding age is necessary for demographic studies, policy formulation, and planning for development. Age data in the census suffers from secondary data due to preferential digit biases and age heaping, contributing to inconsistencies and reliability of Nepal's census data. These discrepancies emphasize the need for a systematic data quality assessment. Methods The present study uses secondary data from the National Population and Housing Census 2021 using a descriptive analytical approach. Whipple's, Myer's Blended index and UN age-sex accuracy index were used to evaluate the quality of age data. These indices can be measures to examine the degree of digit preference and age heaping in age data. Result Whipple's index shows a calculated score of 148.94 for the ages ending in 0 or 5. Myer's Blended index recorded the deviation score of 9.89, based on the moderate age heaping, while the UN Age-Sex Accuracy score of 21.90 scored the data a moderate level of accuracy. These results indicate there are continuing structural errors in self-reported or proxy persistent structural inconsistencies in self- or proxy-reported age data. Conclusion Despite methodological and technological advancements in the 2021 census, there is the presence of persistent structural, educational, and cultural forces. Improvements in enumerator training, verification of documentation and the civil registration system are critical for improving the reliability of data and enhancing demographic and policy-oriented analysis in Nepal. Novelty This paper provides a national-level assessment of age data quality using the 2021 census, providing information for future assessments beyond Nepal's demographic data.